The Association Between Preoperative Serum Thyroid-Stimulating Hormone and Neutrophil-Lymphocyte Ratio as Predictors of Papillary Thyroid Cancer - Stevenson, William; Lumintang, Nico; Tandililing, Sherly; Wariki, Windy Mariane (JBN (Jurnal Bedah Nasional), 2025)
Aim : This study aims to evaluate the correlation between blood thyroid stimulating hormone levels and neutrophil lymphocyte ratio prior to thyroidectomy in patients with papillary thyroid cancer, as well as the potentiality of those as predictors of papillary thyroid cancer. Methods: Thyroid nodule patients over the age of 18 who received treatment at Prof. Dr. R.D. Kandou General Hospital between 2020 and 2024 and who fulfilled the requirements for research inclusion underwent thyroidectomy surgery. The study used a retrospective, descriptive-analytical strategy. Results: The association between TSHs and papillary thyroid cancer was significant with a p-value of 0.025, sensitivity of 51.1%, and specificity of 73.9%; the ROC analysis was performed for TSHs with the results of the AUC value analysis = 0.634 (95% CI: 0.518 – 0.749) with p value = 0.028; NLR and papillary thyroid cancer was significant with a p-value <0.001, sensitivity of 68.9%, and specificity of 100%; the ROC analysis was performed for NLR values with the results of the AUC analysis value = 0.852 (95% CI: 0.766-0.938) with p value = <0.001. Conclusion: NLR is advised as a better predictor of papillary thyroid cancer than TSHs.